2017
DOI: 10.1016/j.neuron.2017.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation-Induced Homeostatic Spine Scaling In Vivo Is Localized to Dendritic Branches that Have Undergone Recent Spine Loss

Abstract: SummarySynaptic scaling is a key homeostatic plasticity mechanism and is thought to be involved in the regulation of cortical activity levels. Here we investigated the spatial scale of homeostatic changes in spine size following sensory deprivation in a subset of inhibitory (layer 2/3 GAD65-positive) and excitatory (layer 5 Thy1-positive) neurons in mouse visual cortex. Using repeated in vivo two-photon imaging, we find that increases in spine size are tumor necrosis factor alpha (TNF-α) dependent and thus are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
103
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 74 publications
15
103
2
Order By: Relevance
“…Homeostatic synaptic scaling was first demonstrated in neurons cultured from rat visual cortex (Turrigiano et al, 1998). It has since been demonstrated in vivo in the visual cortex (Barnes et al, 2017;Desai et al, 2002;Hengen et al, 2013;Keck et al, 2013;Wallace and Bear, 2004) and during sleep (Diering et al, 2017). A recent study, however, demonstrated that visual deprivation by eyelid suture elevates spontaneous activity and lowers the threshold for LTP, a form of homeostatic plasticity distinct from synaptic scaling called "metaplasticity," or the sliding threshold model (Bridi et al, 2018).…”
Section: Homeostatic Plasticity In Vitro Versus In Vivomentioning
confidence: 99%
“…Homeostatic synaptic scaling was first demonstrated in neurons cultured from rat visual cortex (Turrigiano et al, 1998). It has since been demonstrated in vivo in the visual cortex (Barnes et al, 2017;Desai et al, 2002;Hengen et al, 2013;Keck et al, 2013;Wallace and Bear, 2004) and during sleep (Diering et al, 2017). A recent study, however, demonstrated that visual deprivation by eyelid suture elevates spontaneous activity and lowers the threshold for LTP, a form of homeostatic plasticity distinct from synaptic scaling called "metaplasticity," or the sliding threshold model (Bridi et al, 2018).…”
Section: Homeostatic Plasticity In Vitro Versus In Vivomentioning
confidence: 99%
“…This fast, the postsynaptic neuron at any time, which leads to a competition for these building 118 blocks between synapses of the same type [44]. Although there exists evidence for SN in 119 glutamatergic and GABAergic synapses [27,28,43] as well as slow scaling [9,45] within 120 dendritic branches [46], we make the assumption that the SN in these synapses is fast, 121 and that the homeostatic change depends on the weight in a multiplicative fashion [44]. 122 The SN works as follows: all excitatory (inhibitory) weights onto a neuron are regularly 123 updated as 124 w e,j → w e,j 1 + η SN T e,e Ke m=1 w e,m…”
mentioning
confidence: 99%
“…The regulating process involves an enhanced accumulation of AMPAR in the postsynaptic membrane, which can be mediated by the pro-inflammatory cytokine tumour-necrosis factor-α (TNF-α) produced by glia (Stellwagen and Malenka, 2006), the immediate-early gene Arc (Shepherd et al, 2006), β3 integrins (Cingolani et al, 2008) and other molecules. Crucially, the scaling is bidirectional, global and operates in a multiplicative manner (Turrigiano et al, 1998), although there is some evidence for dendritic-branch specific scaling in some neocortical cell types (Barnes et al, 2017). During recovery, multiplicative scaling potentiates synaptic weights within assemblies more than across assemblies in our model, preserving the relative strength of synaptic inputs and enabling the recovery of correlation structure.…”
Section: Discussionmentioning
confidence: 84%